2017
DOI: 10.1002/chem.201704755
|View full text |Cite
|
Sign up to set email alerts
|

From a Metastable Layer to a Stable Ring: A Kinetic Study for Transformation Reactions of Li2Mo3TeO12 to Polyoxometalates

Abstract: A metastable tellurite, Li Mo TeO , revealing a corrugated layered structure in an extremely strained coordination environment was hydrothermally synthesized in high yield. Li Mo TeO undergoes Li -exchange-driven facile structural transformation reactions to polyoxometalates. The kinetic data for the transformation reactions at various conditions were successfully obtained by simple lab-source powder X-ray diffraction. The investigation suggests that the solid-state transformation reactions may occur through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
(4 reference statements)
1
9
0
Order By: Relevance
“…Ag 2 Mo 3 SeO 12 (Ling & Albrecht-Schmitt 2007), Li 2 Mo 3 TeO 12 (Oh et al, 2018) and A 4 Mo 6 Te 2 O 24 Á6H 2 O (A = Rb, K) (Vidyavathy Balraj & Vidyasagar 1998) compounds are quaternary selenite and tellurites of molybdenum, whose [Mo 3 XO 12 ] 2À (X = Se, Te) anionic framework structures are not related to HTO. They have centrosymmetric layered and zero-dimensional structures and contain pyramidally coordinated Se 4+ and pyramidally and disphenoidally coordinated Te 4+ ions.…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Ag 2 Mo 3 SeO 12 (Ling & Albrecht-Schmitt 2007), Li 2 Mo 3 TeO 12 (Oh et al, 2018) and A 4 Mo 6 Te 2 O 24 Á6H 2 O (A = Rb, K) (Vidyavathy Balraj & Vidyasagar 1998) compounds are quaternary selenite and tellurites of molybdenum, whose [Mo 3 XO 12 ] 2À (X = Se, Te) anionic framework structures are not related to HTO. They have centrosymmetric layered and zero-dimensional structures and contain pyramidally coordinated Se 4+ and pyramidally and disphenoidally coordinated Te 4+ ions.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Ag 2 Mo 3 SeO 12 (Ling & Albrecht-Schmitt 2007), Li 2 Mo 3 TeO 12 (Oh et al, 2018) In this context, the structural characterization of new and known quaternary A 2 W 3 SeO 12 (A = NH 4 , Cs, Rb, K, Tl) selenites of tungsten(VI) by single-crystal X-ray diffraction was considered necessary for their complete structural study and, therefore, was undertaken. This report is concerned with crystal growth by solid-state reactions and structural characterization of the known compounds A 2 W 3 SeO 12 [A = NH 4 (1), Cs (2) and Rb (3)] and new compounds K 2 W 3 SeO 12 (4a) and Tl 2 W 3 SeO 12 (5).…”
Section: Chemical Contextmentioning
confidence: 99%
“…It is reported that combination of two different functional units to one compound is an effective method to create novel NCS and SHG materials. Additionally, different building blocks are suitable for producing brand new anion frameworks and enrich the structure chemistry of the inorganic compounds. We have been interested in assembling lone-pair electrons and tetrahedral groups together to make new NCS architectures and SHG materials for decades. The LPE groups were focused on selenite or tellurite containing Se­(IV) or Te­(IV) cations. We created the first boroselenite B 2 Se 2 O 7 , which is composed of SeO 3 triangle pyramids and BO 4 tetrahedra and crystallized in the chiral space group of P 2 1 2 1 2 1 .…”
Section: Introductionmentioning
confidence: 99%
“…If the degree of protonation is in the range between 1.0 and 2.0, many molybdenum atoms can be condensed into polyatomic anions such as Mo 7 O 24 6− to form polyoxomolybdates. Recently, our research group proposed a reaction mechanism for an alkali‐metal‐cation‐induced transformation toward a polyoxomolybdate, the structure of which was verified by means of powder X‐ray diffraction analysis . Molybdates can also be easily combined with a variety of organic molecules by controlling the specific experimental conditions to form organic–inorganic hybrid materials .…”
Section: Introductionmentioning
confidence: 99%
“…Recently,o ur research group proposedareaction mechanism for an alkali-metal-cation-induced transformation towardapolyoxomolybdate, the structure of which was verifiedb ymeansofp owder X-ray diffraction analysis. [8] Molybdates can also be easily combined with av ariety of organic molecules by controlling the specific experimental conditions to form organic-inorganic hybrid materials. [9] Notably,afew interesting examples of chiralh ybrid materials containing organic ligands or counter cationsh ave been reported.…”
mentioning
confidence: 99%